Indonesian Literary Genres Reading Preference of Students from Polytechnic University of the Philippines, Department of English Foreign Languages and Linguistics as a Tool and Aid in Learning Bahasa Indonesia - Amado Gonzales Japsay; Frances Fae Villanueva; Shery Ann Luaton; Cherry Brina (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2022)
Developing the cognitive process of learning foreign languages, language learners are encouraged to seek for ways or tools to make their learning convenient and inspiring, perceiving that the benefits of language learners derives from applying literary text, especially, if the language is embedded deeply in the culture of the society. This study aims to seek literary genre preferences as reading interest of foreign students from the Polytechnic University of the Philippines to aid in an active process of continuous learning Bahasa Indonesia, as it cognitively, continuously affects each foreign student in learning the language, in which it helps every learner to easily retain, remember, and apply lessons and expressions of Bahasa Indonesia, specially, constructing sentence structure, utilizing traditional expressions, and cultural awareness.